TRADISI KLIWONAN: AKULTURASI BUDAYA ISLAM JAWA - Muhamad Taufik Hidayat (IBDA` : Jurnal Kajian Islam dan Budaya, 2012)
This article discusses the cultural assimilation of Kliwonan traditionwith Islamic teachings. Author took some views of Clifford Geertz toexplore the phenomenon of Kliwonan tradition. In that way, it is understoodthat there is a correlation between the pattern of Javanese life withthe teachings of Islam as something noble. Kliwonan done congregationaltradition and intimacy occurs between them. People who do become traditionKliwonan feel close to the Creator, the Almighty God. Tradition asa medium to get closer through the inner region.